2015
DOI: 10.1111/jrh.12130
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant Events, Hopelessness, and Quality of Life in Rural Older Adults

Abstract: Targeting both hopelessness and engagement in pleasant events may be helpful in improving the quality of life of vulnerable, rural older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…One vulnerable demographic group that has been affected at a greater proportion by the mentioned rural drug trends are women; more specifically, economically disadvantaged rural women (Appalachian Regional Commission (ARC), 2016; Browne, 2016; Staton-Tindall et al, 2015a; Staton-Tindall et al, 2015b). Economic distress increases the likelihood that individuals from this Appalachian region will have low social capital, greater health disparities, and limited environmental resources (Marmot & Bell, 2009).…”
Section: A Vulnerable Population: Rural Appalachian Womenmentioning
confidence: 99%
See 3 more Smart Citations
“…One vulnerable demographic group that has been affected at a greater proportion by the mentioned rural drug trends are women; more specifically, economically disadvantaged rural women (Appalachian Regional Commission (ARC), 2016; Browne, 2016; Staton-Tindall et al, 2015a; Staton-Tindall et al, 2015b). Economic distress increases the likelihood that individuals from this Appalachian region will have low social capital, greater health disparities, and limited environmental resources (Marmot & Bell, 2009).…”
Section: A Vulnerable Population: Rural Appalachian Womenmentioning
confidence: 99%
“…factors to have been found to increase the likelihood of accessing treatment (Gelberg et al, 2000; Oser et al, 2016; Rhoades, Winetrobe, & Rice, 2014; Varga & Surratt, 2014). Factors such as social support (Cucciare et al, 2016; Xu et al, 2016), regular sources of health care (Browne et al, 2016), and other barriers not otherwise specified (e.g., stigma of treatment, and access to health insurance) (Appalachian Regional Commission, 2016; Schoeneberger, Leukefeld, Hiller, & Godlaski, 2006). In addition, researchers have found that drug-using women with more positive attitudes regarding treatment services resulted in a greater likelihood of help-seeking behavior (Segal, Coolidge, Mincic, & O’Riley, 2005).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the individual subjective side, the QoL is seen as a broad term encompassing the notions of a good life, a valued life, a satisfying life, and a happy life (Diener & Suh, 1997;Feneri et al, 2013;Henchoz et al, 2015;Scogin, Morthland, DiNapoli, LaRocca, & Chaplin, 2016). The concepts of a satisfying life and a happy life could be combined into the subjective well-being (McCrea et al, 2006) or individually perceived / experienced subjective QoL.…”
Section: The Complex Of Individual Subjectively Perceived Qol Factorsmentioning
confidence: 99%